Characterization of human thymic exosomes. - Gabriel Skogberg; Judith Gudmundsdottir; Sjoerd van der Post; Kerstin Sandström; Sören Bruhn; Mikael Benson; Lucia Mincheva-Nilsson; Vladimir Baranov; Esbjörn Telemo; Olov Ekwall (PLoS ONE, 2013)
Exosomes are nanosized membrane-bound vesicles that are released by various cell types and are capable of carrying proteins, lipids and RNAs which can be delivered to recipient cells. Exosomes play a role in intercellular communication and have been described to mediate immunologic information. In this article we report the first isolation and characterization of exosomes from human thymic tissue. Using electron microscopy, particle size determination, density gradient measurement, flow cytometry, proteomic analysis and microRNA profiling we describe the morphology, size, density, protein composition and microRNA content of human thymic exosomes. The thymic exosomes share characteristics with previously described exosomes such as antigen presentation molecules, but they also exhibit thymus specific features regarding surface markers, protein content and microRNA profile. Interestingly, thymic exosomes carry proteins that have a tissue restricted expression in the periphery which may suggest a role in T cell selection and the induction of central tolerance. We speculate that thymic exosomes may provide the means for intercellular information exchange necessary for negative selection and regulatory T cell formation of the developing thymocytes within the human thymic medulla.